Investigations on Hemolysis in Cows with Tropical Theileriosis - Basbug, Onur; Gul, Yusuf (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
In this study, it was aimed to detect the severity and the type of the haemolysis that effect the anemia formation in the cows with tropical theileriosis. Totally 40 cultured strains and their crossbreeds as 10 healthy cattles and 30 cattles infected with Theileria annulata were used in this study. Patient cattles were separated into 3 equal groups according to the anemia level as mild, moderate and severe. Erythrocyte number, hemoglobin concentration, hematocrit value, total leukocyte numbers and reticulocyte counting were detected. Total bilirubine, indirect bilirubine, AST and LDH levels were measured in sera. Serum amyloid A and haptoglobin analysis were done. The physical and quantitatively examining of the urina were done. Urine sediment was also examined with a dark field microscobe in tems of leptospria. The significant differences among the groups in terms of clinical (body temperature, heart and respiration frequencies, rumen movements), hematological (erythrocyte number, hemoglobin concentration, hematocrit value and total leukocyte numbers) and biochemical (total bilirubine, indirect bilirubine, AST and LDH, SAA and haptoglobin levels) parameters of the working animals were determined. Although it is not statistically significant, the reticulocyte numbers increased at the moderate and severe anemia groups. Hemoglobinuria was not seen in any of the diseased animals. As a result, hemolysis, which plays a role in the patogenesis of the anemia with the tropical theileriosis caused by T. annulata, is extravascular type and its severity increases as well as the disease progress.
Tropikal tayleriyozisli sı?ırlarda hemoliz üzerine araştırmalar
Keywords: Cattle; Theileria annulata; Tropical theileriosis; Hemolysis; Anemia